Intranasal as needed naloxone in the treatment of gambling disorder: A randomised controlled trial - Alho Hannu; Mäkelä Niklas; Isotalo Jarkko; Toivonen Lilianne; Ollikainen Jyrki; Castrén Sari (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Background: Gambling disorder (GD) is a global phenomenon affecting millions of people. GD can result in severe social and financial difficulties and efficacious treatments are warranted. Psychosocial treatments form the basis of treatment. Opioid antagonists (OAs) have however shown promise in previous studies. In a recent imaging study intranasal naloxone was found to rapidly and fully occupy brain mu-opioid receptors. This trial investigates the effect and safety of as needed naloxone in the treatment of gambling disorder.
Methods: This was a 12-week double blind, randomised control trial comparing intranasal naloxone to placebo. The primary endpoint was gambling urge measured by the Gambling symptom Assessment Scale (G-SAS). Secondary outcome measures were gambling severity measures (PGSI) as well as quality of life (WHO:EUROHIS-8), alcohol consumption (AUDIT), depression (MARDS) and internet use (IDS-9SF). In addition, safety of treatment was assessed. Both treatment groups received psychosocial support.
Results: 126 participants were randomised to treatment groups in a 1:1 ratio. 106 patients completed the study. Gambling urge (GSAS) and other gambling related measured improved in both groups, but no statistically significant difference could be found. Intranasal naloxone was well tolerated, no subjects discontinued the study due to adverse events. No serious adverse drug reactions were observed.
Conclusions: This study found no difference between the as-needed administration of intranasal naloxone and placebo in reducing gambling urge in persons with GD. Intranasal naloxone was safe and well tolerated.